Proses dan Makna Pacaran di Kalangan Mahasiswa: Studi Fenomenologi - Andi Tiara Nurul Izzah Fathia; Erna Herawati (Umbara, 2023)
Dating among youth is an interesting social phenomenon as two individu aggre to engage in a dyadic and romantic social interaction. Dating, from the beginning to its end,  illustrates the cycle of dynamic social interaction which is full of symbolism. This research uses perspective of social interaction and symbolic interactionism theory to analyse dating among university students and how they attach meaning to dating. Using a qualitative-phenomenology design, this research collected primary data through indepth interviews. Findings of this research suggest that the cycle of dating is similar to social interaction. It started with asosiative activities, such as introduction and some initial activities before the decision to date has been made. Some activities during dating symbolize the implementation of the agreement between two indivuals. Meanwhile, some disosiative activities symbolize the discontinuation of the agreement between them. Students consider dating as casual and simple social interaction rather than a courship that lead to marriage.